Comparing therapeutic outcomes: radioactive iodine therapy versus non-radioactive iodine therapy in differentiated thyroid cancer - Tiucă, Robert Aurelian; Tiucă, Oana Mirela; Pop, Raluca Monica; Paşcanu, Ionela Maria (Frontiers in Endocrinology, 2024)
significantly protected against incomplete biochemical control in the overall population (p = 0.019) and in patients with histological indolent DTC (p = 0.030). Predictive factors for incomplete biochemical control included male sex (p = 0.008) and incomplete structural control (p = 0.002) across all patients, regardless of the histological type.While RAI therapy has traditionally been used to manage DTC, our study found no significant difference in biochemical and structural responses between patients who received RAI therapy and those who did not. However, RAI therapy emerged as a protective factor against incomplete biochemical control, even in histological indolent DTC cases. These findings suggest that while RAI therapy may not be universally necessary, it could be beneficial in reducing the risk of biochemical recurrence in select patient subgroups, such as those with incomplete structural control or male patients. Thus, a personalized approach to RAI therapy, tailored to individual risk factors, may improve patient outcomes without overtreatment.RAI therapy can provide long-term benefits across all histological types of differentiated thyroid cancer (DTC). By lowering the likelihood of a biochemical incomplete response, it might effectively diminish the risk of cancer recurrence. Therefore, incorporating RAI therapy into the treatment plan for DTC patients may improve the overall prognosis and long-term survival rates.